An Investigation into the implementation of distributed leadership in English Schools - Sired, Craig (2008)
Abstract Purpose: The purpose of this dissertation is to research into the relationship between distributed leadership and school performance and also to see in what context the enactment of distributed leadership is likely to flourish. Approach: The research uses 358 secondary schools in England to represent a typical public sector organisation. A thorough and systematic review of the literature is undertaken to develop an understanding of the concept before Ofsted reports are used to test whether distributed leadership is being displayed or not. The inductive approach will then test the distribution of leadership with various variables as the dissertation will attempt to shed some light on the phenomenon. Findings: Relatively little correlation was identified between school performance and the distribution of leadership. However, certain characteristics were found prevalent in assisting the enactment of distributed leadership and therefore enhanced our knowledge on the topic. In particular the social and cultural context as well as the location of the school played an important part in determining the level of distribution.